Genome-Wide Association Study of Resistance to Phytophthora capsici in the Pepper (Capsicum spp.) Collection - Ro, Nayoung; Haile, Mesfin; Hur, Onsook; Geum, Bora; Rhee, Juhee; Hwang, Aejin; Kim, Bitsam; Lee, Jeaeun; Hahn, Bum-Soo; Lee, Jundae; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2022)
One of the most serious pepper diseases is Phytophthora blight, which is caused by Phytophthora capsici. It is crucial to assess the resistance of pepper genetic resources to Phytophthora blight, understand the genetic resistances, and develop markers for selecting resistant pepper materials in breeding programs. In this study, the resistance of 342 pepper accessions to P. capsici was evaluated. The disease severity score method was used to evaluate the phenotypic responses of pepper accessions inoculated with the KCP7 isolate. A genome-wide association study (GWAS) was performed to identify single nucleotide polymorphisms (SNPs) linked to P. capsici (isolate KCP7) resistance. The pepper population was genotyped using the genotype-by-sequencing (GBS) method, and 45,481 SNPs were obtained. A GWAS analysis was performed using resistance evaluation data and SNP markers. Significantly associated SNPs for P. capsici resistance at four weeks after inoculation of the GWAS pepper population were selected. These SNPs for Phytophthora blight resistance were found on all chromosomes except Chr.05, Chr.09 and Chr.11. One of the SNPs found on Chr.02 was converted into a high-resolution melting (HRM) marker, and another marker (QTL5-1) from the previous study was applied to pepper accessions and breeding lines for validation and comparison. This SNP marker was selected because the resistance phenotype and the HRM marker genotype matched well. The selected SNP was named Chr02-1126 and was located at 112 Mb on Chr.02. The Chr02-1126 marker predicted P. capsici resistance with 78.5% accuracy, while the QTL5-1 marker predicted resistance with 80.2% accuracy. Along with the marker for major quantitative traits loci (QTLs) on Chr.05, this Chr02-1126 marker could be used to accurately predict Phytophthora blight resistance in pepper genetic resources. Therefore, this study will assist in the selection of resistant pepper plants in order to breed new phytophthora blight-resistant varieties.